Hyperosmolar Hyperglycemic State (HHS) and Diabetic Kidney Disease (DKD) as Acute and Chronic Complications of Type 2 Diabetes Mellitus in End-Stage Chronic Kidney Disease (CKD): a Case Report - Ni Putu Radha Premaiswari Suparthika; Nyoman Sutarka (Al Makki Health Informatics Journal, 2025)
Introduction: Hyperosmolar hyperglycemic state (HHS) is a life-threatening condition that often occurs in patients with type 1 and 2 diabetes mellitus characterized by hyperglycemic crises, hyperosmolarity, dehydration, with mild ketosis or no eketosis. Another chronic complication of Diabetes Mellitus is Diabetic Kidney Disease (DKD). Ni Putu Radha Premaiswari Suparthika1, I Nyoman Sutarka. Case Presentation: A 61-year-old male patient was referred with decreased consciousness since 5 days of SMRS. The patient has a history of type 2 diabetes mellitus since 20 years. In patients, signs were obtained in the form of decreased consciousness, severe hyperglycemia of 680 mg/dL, hyperosmolarity of 360 mOsm/kg, increase in anion gap >12, UTI complications as the trigger of HHS. In patients, moderate anemia was also found normochromic-normocyter, massive proteinuria, and decreased kidney function. Conclusion: In the 61-year-old male patient described in this case report, there are acute and chronic complications of Diabetes Mellitus that occur simultaneously and have caused high morbidity and mortality in patients.